Exploring The Fatwa methodology of committee of The National Council for Islamic Affairs: Case of ASB Trust Fund - Sitiris, Miszairi; Mahmud, Mek Wok; Zakaria, Mohamad Sabri; Busari, Saheed Abdullahi (World Fatwa Management and Research Institute (INFAD), Universiti Sains Islam Malaysia (USIM), 2020)
Amanah Saham Bumiputera (ASB) is a Malaysian initiative trust fund that was established in 1990 with the basic aim of enhancing the financial independence and improves the economic control of the Bumiputera Malaysians. This effort has provided investment opportunity for its target audience as an alternative savings scheme in order to generate long term consistent and competitive returns on investment. Despite the achievement and successful result recorded by the establishment, there are continuous quest particularly among the Bumiputera on the extent of Shariah compliance of the investment channels of ASB trust fund. Although ASB was designed as a fixed price equity income fund at RM1.00 with no sale charges, the return on investment as declared dividend is questionable. More so, the means of investment and in which product or services to invest pool fund is a question for debate among the investors. Despite the latest Fatwa MKI pronouncement by Muzākarah Jawatankuasa on this issue in 2012, which declared that investments in ASB and other relative investments are ‚harus‛, that is investing in ASB is neither prohibited nor allowed from an Islamic perspective. It is rather Mubāḥah; based on free choice. Hence, there are still arguments as to whether ASB is prohibited in Islam. The researcher therefore aims to explore into the methodology of the Fatwa committee of the National Council for Islamic Affairs on how and why permissible position was taken in comparison with the position of PNB on its permissibility. The study also conducts textual analysis on Islamic principles, maxims and conditions on issuing fatwa on matters relating to Islamic financial transactions as reported in Islamic literatures. The study also employs the Maqāṣid shariah approach and found out that the decision the current which permits ASB investment for muslims in Malaysia was as a result re-consultation and research among the shariah scholars and ASB stakeholders to arrive at a common ground on the use of maṣlaḥah as evidence for the permissibility of the ASB in Malaysia context.